ES composite fiber for dry-process dust-free paper and preparation method thereof
By using modified PE/PP composite fibers in dust-free ultrashort fibers, the problems of insufficient bonding effect, hygroscopicity and dispersion are solved, better looseness and longitudinal strength are achieved, and the overall performance of dust-free paper is improved.
Patent Information
- Application Number
- CN202411383378.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The existing dust-free paper has shortcomings in the bonding effect, hygroscopicity and dispersion of ultrashort fibers, which affects its looseness and longitudinal strength.
PE/PP is used as the main raw material for production, and by adding lower melting masterbatches and antistatic masterbatches to the cortical raw materials, they are modified in terms of moisture absorption, bonding, and antistatic functions, and ES composite fibers suitable for dry dust-free paper are prepared.
It improves the bonding effect and moisture absorption performance of ultra-short fibers, enhances dispersion, meets the requirements of dust-free paper for moisture absorption, and improves the looseness and longitudinal strength of the product.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of composite fibers, and in particular to ES composite fibers for dry-laid dust-free paper and a preparation method thereof. Background Art
[0002] Expanded soft paper (dust-free paper) produced by dry papermaking is the lining paper of disposable sanitary materials. It can absorb liquid 3-5 times its volume without reverse osmosis, so it has been well developed in China in recent years. The production of dust-free paper is divided into chemical bonding and thermal bonding. The thermal bonding method is to use hot air or hot rolling to evenly bond the low melting point in the fiber web with water-absorbing materials such as wood pulp, abandoning the traditional production process of using chemical adhesives to bond wood pulp fibers in the past production of dust-free paper, and truly achieving the effect of no adverse reactions to human skin.
[0003] At present, the development of dust-free paper is mainly to improve the performance of dust-free paper by improving process parameters, but there are relatively few improvements on its important raw material ultra-short fibers. The quality of ultra-short fiber bonding is directly related to the physical indicators of dust-free paper such as bulkiness and longitudinal strength. How to obtain a short fiber with high bonding strength and good hygroscopicity suitable for dry-process dust-free paper is the research focus of this application. Summary of the invention
[0004] In view of the shortcomings in the prior art, the present invention utilizes the advantage of the non-toxicity of the PE / PP production raw materials themselves and modifies their moisture absorption, bonding, antistatic and other functions, so that the ultra-short fibers used for bonding have both good bonding effects and certain moisture absorption properties and good dispersibility, which meets the moisture absorption requirements of dust-free paper and improves the product grade.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] An ES composite fiber for dry-process dust-free paper, the raw materials comprising 40-45 parts by weight of component A: 75-85wt% HDPE, 10-15wt% melt-reducing masterbatch, 5-10wt% antistatic masterbatch; and 55-60 parts by weight of component B: PP;
[0007] The preparation process of the melt-reducing masterbatch is as follows:
[0008] S1, mesoporous silica is dispersed in a methanesulfonic acid aqueous solution, heated to 90°C, stirred and refluxed overnight, cooled, washed and filtered, then mixed evenly with γ-aminopropyltrimethoxysilane in water, heated to 50°C, stirred for 24h, cooled to room temperature, filtered, rinsed with ethanol, and dried to obtain amino mesoporous silica;
[0009] S2, synthesizing hyperbranched polymers through RAFT system using vinyl acetate, ethyl acrylate and acrylic acid as monomers, AIBN as initiator and xanthate containing terminal double bonds as chain transfer agent;
[0010] S3, dispersing and dissolving the products of step S1 and step S2 in tetrahydrofuran respectively, then mixing the two, stirring and refluxing overnight under a nitrogen atmosphere, then centrifuging, washing the obtained product with ethanol and water, and vacuum drying to obtain hyperbranched polymer mesoporous silica;
[0011] S4, dissolving maleic anhydride, polyethylene glycol methacrylate and an initiator in tetrahydrofuran, then adding hyperbranched polymer mesoporous silica and PE and mixing evenly, extruding through a reactive twin-screw extruder, pelletizing and drying to obtain;
[0012] The preparation process of the antistatic masterbatch is as follows:
[0013] Maleic anhydride and initiator are dissolved in acetone, and then graphene oxide is treated with γ-methacryloxypropyltrimethoxysilane and dispersed therein, stirred evenly and mixed evenly with PE, extruded by reaction through a reactive twin-screw extruder, pelletized and dried.
[0014] Furthermore, in step S1, the mass volume ratio of mesoporous silica to γ-aminopropyltrimethoxysilane is 1:1.
[0015] Furthermore, in step S2, the xanthate containing a terminal double bond is (2-ethoxydithioate) vinyl acetate; the molar ratio of vinyl acetate, butyl acrylate, acrylic acid, AIBN and the xanthate containing a terminal double bond is 100:10~50:50~90:0.5:1.
[0016] Furthermore, in step S3, the dosage ratio of the products of step S1 and step S2 is 0.05-0.1:1.
[0017] Furthermore, in step S4, the mass ratio of maleic anhydride, polyethylene glycol methacrylate, initiator, hyperbranched polymer mesoporous silica and PE is 5-10:4-8:0.5-1:1-5:90.
[0018] Furthermore, in the preparation process of the antistatic masterbatch, the processing steps of graphene oxide are: ultrasonically dispersing graphene oxide in an aqueous solution, adding ammonia water to adjust the pH to alkaline, continuing ultrasound, then adding an equal amount of γ-methacryloxypropyltrimethoxysilane, raising the temperature to 60°C and stirring overnight, after the reaction is completed, centrifugally separating, washing with ethanol and water, and then vacuum drying.
[0019] Furthermore, in the preparation process of the antistatic masterbatch, the mass ratio of maleic anhydride, initiator, treated graphene oxide and PE is 5-10:0.5-1:1-5:90.
[0020] The second object of the present invention is to provide a method for preparing ES composite fibers for dry-laid dust-free paper, comprising the following steps:
[0021] Pre-spinning process: the raw materials of the skin layer and the core layer are respectively fed into two screw extruders through two feeding hoppers to be melted and extruded into melts. After filtering, they are closely metered into the spinning box by the metering pump and come to the spinning assembly to form raw silk with skin-core structure.
[0022] Post-spinning process: The raw silk that is traversed from the front spinning is bundled and passed through an oil immersion tank, a steam preheating box, a water bath, three drafting, an oiling roller, a crimping machine, a relaxation heat setting machine, and cut into ultra-short fibers of the required size.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: PE / PP is selected as the main raw material for production in this case, which has the advantage of being non-toxic. By adding masterbatch that can lower the melting point and improve the antistatic property to the cortical raw material, the moisture absorption, bonding, antistatic and other functions are modified, so that the ultra-short fibers used for bonding have both good bonding effect and certain moisture absorption performance and good dispersibility, which meets the moisture absorption requirements of dust-free paper. Using this kind of fiber in the production of expanded soft paper can make the paper feel plump, the bulkiness is good, the moisture absorption effect is significantly improved, the product will be brand new, and it is an ideal material for sanitary products. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0026] Example: ES composite fiber for dry-laid dust-free paper
[0027] The raw materials include 40-45 parts by weight of component A: 75-85wt% HDPE, 10-15wt% melt-reducing masterbatch, 5-10wt% antistatic masterbatch; and 55-60 parts by weight of component B: PP;
[0028] The preparation process includes pre-spinning procedure and post-spinning procedure:
[0029] Pre-spinning process: the raw materials of the skin layer and the core layer are respectively fed into two screw extruders through two feeding hoppers to be melted and extruded into melts. After filtering, they are closely metered into the spinning box by the metering pump and come to the spinning assembly to form raw silk with skin-core structure.
[0030] Post-spinning process: The raw silk that is traversed from the front spinning is bundled and passed through an oil immersion tank, a steam preheating box, a water bath, three drafting, an oiling roller, a crimping machine, a relaxation heat setting machine, and cut into ultra-short fibers of the required size.
[0031] In this application, the main raw material HDPE is selected from Dow Chemical 8920, LG 9180 or Fujian United 8920, PP is selected from Yangzhou Petrochemical 150 powder, and the melt-reducing masterbatch and antistatic masterbatch are self-made by the applicant. The preparation process is shown below.
[0032] The main equipment in this application: front spinning machine, Neumag Company, Germany; post-spinning combined processing machine, Shaoyang No. 2 Textile Machinery.
[0033] The preparation process of the melt-reducing masterbatch is as follows:
[0034] S1. Dissolve 2g of template P123 in hydrochloric acid solution, and finally add 4.5g of ethyl orthosilicate dropwise, stir at 40°C to form an organosilicon sol, and then stand at 90°C for 24h, centrifuge and vacuum dry to obtain mesoporous silica;
[0035] 2g of mesoporous silica was dispersed in 10ml of 5% methanesulfonic acid aqueous solution, heated to 90℃, stirred and refluxed overnight, cooled, washed and filtered, then mixed evenly with 2ml of γ-aminopropyltrimethoxysilane in water, heated to 50℃, stirred for 24h, cooled to room temperature, filtered, rinsed with ethanol, and dried to obtain amino-modified mesoporous silica;
[0036] S2, synthesizing a hyperbranched polymer through a RAFT system using 1 mol of vinyl acetate, 200 mmol of ethyl acrylate and 800 mmol of acrylic acid as monomers, 5 mmol of AIBN as an initiator, and 10 mmol of xanthate containing a terminal double bond ((2-ethoxydithioate) vinyl acetate, prepared by referring to patent 201010223709.X) as a chain transfer agent;
[0037] S3, dispersing and dissolving the products of step S1 and step S2 in tetrahydrofuran respectively, then mixing the two, stirring and refluxing overnight under a nitrogen atmosphere, then centrifuging, washing the obtained product with ethanol and water, and vacuum drying to obtain hyperbranched polymer mesoporous silica;
[0038] S4, dissolve maleic anhydride, polyethylene glycol methyl methacrylate and initiator in tetrahydrofuran, then add hyperbranched polymer mesoporous silica and PE and mix evenly, extrude through a reactive twin-screw extruder, cut into pellets and dry to obtain. (The mass ratio of maleic anhydride, polyethylene glycol methyl methacrylate, initiator, hyperbranched polymer mesoporous silica and PE is 5~10:4~8:0.5~1:1~5:90)
[0039] When the other conditions remain unchanged, the mass ratio in step S4 is adjusted to obtain the following descending melt masterbatch:
[0040] Sample 1: The mass ratio of maleic anhydride, polyethylene glycol methyl methacrylate, initiator, hyperbranched polymer mesoporous silica and PE is 5:4:0.5:2:90;
[0041] Sample 2: The mass ratio of maleic anhydride, polyethylene glycol methyl methacrylate, initiator, hyperbranched polymer mesoporous silica and PE is 7:6:0.6:3:90;
[0042] Sample 3: The mass ratio of maleic anhydride, polyethylene glycol methyl methacrylate, initiator, hyperbranched polymer mesoporous silica and PE is 8:8:0.8:5:90;
[0043] Sample 4: The mass ratio of maleic anhydride, polyethylene glycol methyl methacrylate, initiator, hyperbranched polymer mesoporous silica and PE is 8:6:0.6:0:90.
[0044] The preparation process of the antistatic masterbatch is as follows:
[0045] Graphene oxide was ultrasonically dispersed in an aqueous solution, ammonia was added to adjust the pH to alkaline, and ultrasonication was continued. Then, an equal amount of γ-methacryloxypropyltrimethoxysilane was added, and the temperature was raised to 60°C and stirred overnight. After the reaction was completed, it was centrifuged, washed with ethanol and water, and then vacuum dried to obtain KH570-rGO.
[0046] Maleic anhydride and initiator are dissolved in acetone, and then KH570-rGO is dispersed therein, stirred evenly, and then mixed evenly with PE, extruded by a reactive twin-screw extruder, pelletized, and dried. (In the preparation process of the antistatic masterbatch, the mass ratio of maleic anhydride, initiator, treated graphene oxide, and PE is 5~10:0.5~1:1~5:90)
[0047] With the other conditions unchanged, the mass ratio in the steps is adjusted to obtain the following antistatic masterbatch:
[0048] Sample I: The mass ratio of maleic anhydride, initiator, treated graphene oxide, and PE is 5:0.5:1:90;
[0049] Sample II: The mass ratio of maleic anhydride, initiator, treated graphene oxide, and PE is 7:0.7:3:90
[0050] Sample III: The mass ratio of maleic anhydride, initiator, treated graphene oxide, and PE is 8:0.9:5:90
[0051] Sample IV: Graphene oxide
[0052] In the above-mentioned process of preparing the melting masterbatch, firstly, the mesoporous silica is amino-modified to form amino active sites on its surface, which can be subjected to amidation reaction, etc.; secondly, the hyperbranched polymer chain containing ester and carboxyl groups is prepared by active free radical polymerization, and the amino-modified mesoporous silica is used as a template to form an organic whole on its surface; then, the organic whole is grafted and polymerized with PE with maleic anhydride under the initiation of an initiator in a reactive twin-screw extruder to form a modified masterbatch with PE as a carrier, which has a mesoporous and three-dimensional network structure. It can reduce the intermolecular force of PE, reduce the interaction force between crystals, reduce the crystallinity, and thus play a role in reducing the melting point. The prepared masterbatch has good dispersibility and compositeness when mixed with PE, avoiding the occurrence of floating silk, broken silk and sizing silk in the production process caused by uneven mixing; in addition, when mixed with PE, maleic anhydride is used as the grafting active site, and polyethylene glycol methyl methacrylate is added. The introduction of long flexible chain polyethylene glycol can further increase the hygroscopicity of the material.
[0053] The antistatic masterbatch is prepared by grafting graphene oxide treated with a silane coupling agent and maleic anhydride on the surface of PE. The antistatic masterbatch has a good mixing effect when mixed with the raw material of the cortex, and the antistatic effect of the material is improved at the same time.
[0054] After the raw materials required for this application are determined, they are used to prepare composite fibers for dry-laid dust-free paper. First, the process parameters of the front spinning and the back spinning are determined as shown in Tables 1 and 2.
[0055] Table 1 Main process parameters of pre-spinning
[0056]
[0057] Post-spinning waterbath drafting multiple
[0058] The fiber structure of the raw silk formed in the spinning process of the pre-spinning raw silk is not tight enough. Considering the control of macromolecular orientation and crystallinity, a large ratio of stretching cannot be performed. Therefore, the post-spinning design performs a low ratio of stretching to improve the fiber orientation not too much and the crystallinity is moderate, which is conducive to the ultimate realization of the best adhesion of the product. The water bath stretching multiple is about 3 times.
[0059] Curl parameter setting
[0060] In order to maximize the bonding performance of the fiber, reducing or even eliminating curling can theoretically increase the contact area and number of contact points between a single fiber and the wood pulp, thereby achieving optimal performance. Therefore, the process is designed based on a curl-free bundle, the curling back pressure is 0, and the main pressure is set to 0.02MPa based on a comprehensive consideration of the tow's passability.
[0061] Table 2 Main process parameters of post-spinning
[0062]
[0063] The selection and proportion of raw materials are shown in Table 3. The mass ratio of raw materials for the skin layer and the core layer is 40:60.
[0064] Table 3
[0065]
[0066] The performance of the fibers prepared in the above embodiments was tested, and the results are shown in Table 4.
[0067] Table 4
[0068]
[0069] It can be seen from Table 4 that the ultra-short fibers produced in the present application have good dispersibility, excellent antistatic properties, greatly improved hygroscopicity, reduced melting point, and improved strength; they have high bonding strength and can be bonded by hot air method to evenly bond them with water-absorbing materials such as wood pulp, thus meeting the hygroscopic requirements of dust-free paper.
[0070] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. An ES composite fiber for dry-laid dust-free paper, characterized in that: The raw materials include 40-45 parts by weight of component A: 75-85wt% HDPE, 10-15wt% melt-reducing masterbatch, 5-10wt% antistatic masterbatch; and 55-60 parts by weight of component B: PP; The preparation process of the melt-reducing masterbatch is as follows: S1, mesoporous silica is dispersed in a methanesulfonic acid aqueous solution, heated to 90°C, stirred and refluxed overnight, cooled, washed and filtered, then mixed evenly with γ-aminopropyltrimethoxysilane in water, heated to 50°C, stirred for 24h, cooled to room temperature, filtered, rinsed with ethanol, and dried to obtain amino mesoporous silica; S2, synthesizing hyperbranched polymers through RAFT system using vinyl acetate, ethyl acrylate and acrylic acid as monomers, AIBN as initiator and xanthate containing terminal double bonds as chain transfer agent; S3, dispersing and dissolving the products of step S1 and step S2 in tetrahydrofuran respectively, then mixing the two, stirring and refluxing overnight under a nitrogen atmosphere, then centrifuging, washing the obtained product with ethanol and water, and vacuum drying to obtain hyperbranched polymer mesoporous silica; S4, dissolving maleic anhydride, polyethylene glycol methacrylate and an initiator in tetrahydrofuran, then adding hyperbranched polymer mesoporous silica and PE and mixing evenly, extruding through a reactive twin-screw extruder, pelletizing and drying to obtain; The preparation process of the antistatic masterbatch is as follows: Maleic anhydride and initiator are dissolved in acetone, and then graphene oxide is treated with γ-methacryloxypropyltrimethoxysilane and dispersed therein, stirred evenly and mixed evenly with PE, extruded by reaction through a reactive twin-screw extruder, pelletized and dried.
2. The ES composite fiber for dry-laid dust-free paper according to claim 1, characterized in that: In the step S1, the mass volume ratio of mesoporous silica to γ-aminopropyltrimethoxysilane is 1:
1.
3. The ES composite fiber for dry-laid dust-free paper according to claim 1, characterized in that: In the step S2, the xanthate containing a terminal double bond is (2-ethoxydithioate) vinyl acetate; the molar ratio of vinyl acetate, butyl acrylate, acrylic acid, AIBN and the xanthate containing a terminal double bond is 100:10-50:50-90:0.5:
1.
4. The ES composite fiber for dry-laid dust-free paper according to claim 1, characterized in that: In the step S3, the dosage ratio of the product of step S1 to that of step S2 is 0.05-0.1:
1.
5. The ES composite fiber for dry-laid dust-free paper according to claim 1, characterized in that: In the step S4, the mass ratio of maleic anhydride, polyethylene glycol methacrylate, initiator, hyperbranched polymer mesoporous silica and PE is 5-10:4-8:0.5-1:1-5:
90.
6. The ES composite fiber for dry-laid dust-free paper according to claim 1, characterized in that: In the preparation process of the antistatic masterbatch, the processing steps of graphene oxide are: ultrasonically dispersing graphene oxide in an aqueous solution, adding ammonia water to adjust the pH to alkaline, continuing ultrasonication, then adding an equal amount of γ-methacryloxypropyltrimethoxysilane, raising the temperature to 60°C and stirring overnight, after the reaction is completed, centrifugally separating, washing with ethanol and water, and then vacuum drying to obtain the masterbatch.
7. The ES composite fiber for dry-laid dust-free paper according to claim 1, characterized in that: During the preparation of the antistatic masterbatch, the mass ratio of maleic anhydride, initiator, treated graphene oxide and PE is 5-10:0.5-1:1-5:
90.
8. The method for preparing ES composite fiber for dry-laid dust-free paper according to any one of claims 1 to 7, characterized in that: The steps include: Pre-spinning process: the raw materials of the skin layer and the core layer are respectively fed into two screw extruders through two feeding hoppers to be melted and extruded into melts. After filtering, they are closely metered into the spinning box by the metering pump and come to the spinning assembly to form raw silk with skin-core structure. Post-spinning process: The raw silk from the front spinning is bundled and passed through an oil immersion tank, a steam preheating box, a water bath, three drafting, an oiling roller, a crimping machine, a relaxation heat setting machine, and cut into ultra-short fibers of the required size.
Citation Information
Patent Citations
Preparation method of hyperbranched polyvinyl acetate
CN101891843B
Preparation method of hyperbranched polyvinyl acetate
CN101891843A
Preparation method of PE-PET composite ultra-short fibers, application and post-spinning system
CN108716027A